(untitled) (Proceedings of Southern Federal University. Philology, 2019)
Natalya B. Boeva-Omelechko (Rostov-on-Don, Russian Federation) The article is topical due to the interest of conflictology to the problem of conflict prevention and de-intensification. The linguistic aspect of this problem presupposes, in particular, identification of the range of verbal conflict stimulants. The latter include questions, functioning in uncooperative discourse based on confrontation, dominance of the speaker over the addressee, breaking norms of politeness. Such questions realize a speech macro-strategy of impoliteness. However the conflictogenic potential of a question was not an object of the special investigation. The article claims that both direct and indirect interrogative speech acts can stimulate the beginning and development of the conflict. Direct interrogative speech acts perform these functions if they do not correspond to the norms of politeness and intrude somebody’s privacy, stimulating the strategy of communicative sabotage. Indirect interrogative speech acts in uncooperative discourse have numerous illocutionary forces and realize speech strategies of verbal aggression, communicative sabotage, discreditation of the opponent and invective strategy. Both questions-stimuli and questions-reactions can serve the means of the realization of the strategies in question. The article reveals speech acts, having a form of a question and corresponding to each of these strategies. It lays the foundation for the investigation of speech acts which ought to follow impolite questions in order to neutralize their conflictogenic potential. Key words: question, conflict, uncooperative discourse, speech strategy, interrogative speech act, impoliteness. DOI 10.23683/1995-0640-2019-1-67-75